2018
DOI: 10.1186/s10194-018-0837-3
|View full text |Cite
|
Sign up to set email alerts
|

The Headache-Attributed Lost Time (HALT) Indices: measures of burden for clinical management and population-based research

Abstract: BackgroundThe burden attributable to headache disorders has multiple components: a simple measure summarising them all does not exist. The Migraine Disability Assessment (MIDAS) instrument has proved useful, estimating productive time lost in the preceding 3 months due to the disabling effect of headache. We developed adaptations of MIDAS for purposes of the Global Campaign against Headache, embracing epidemiological studies and the provision of clinical management aids.MethodsWe reviewed the structure, conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 21 publications
0
45
0
1
Order By: Relevance
“…Steiner et al [35] considered workdays with productivity reduced to 50% or more of the expected productivity as days fully lost. This validated approach counterbalances those working days when the productivity was reduced by less than half of the expected, which are ignored otherwise [40, 41]. As personal impact in terms of lost useful time was surprisingly uniform across European countries [35], had we surveyed individuals suffering from migraine in Latvia and Lithuania might we arrived at very similar estimates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Steiner et al [35] considered workdays with productivity reduced to 50% or more of the expected productivity as days fully lost. This validated approach counterbalances those working days when the productivity was reduced by less than half of the expected, which are ignored otherwise [40, 41]. As personal impact in terms of lost useful time was surprisingly uniform across European countries [35], had we surveyed individuals suffering from migraine in Latvia and Lithuania might we arrived at very similar estimates.…”
Section: Discussionmentioning
confidence: 99%
“…This estimate includes workdays lost both due to sick leave and impairment; the authors estimate total productive time lost at work as the sum of workdays lost completely due to absenteeism and workdays with productivity reduced to 50% or more of the expected productivity. Steiner and Lipton [40] argue that this approach counterbalances those working days when the productivity was reduced by less than half of the expected, which are ignored otherwise. This approach has already been introduced by MIDAS and was validated in [41].…”
Section: Methodsmentioning
confidence: 99%
“…Ascertainment of debilitating attacks shall be done with clinical interview or with the use of validated scales in order to evaluate if headaches significantly interfere with a patient's ability to work, attend school, or participate in family or social activities. The EHF Expert Consensus Group did not choose to use cut scores at common validated instruments to measure function or disability such as the MIgraine Disability ASsessment (MIDAS) tool [19], the Headache Impact Test (HIT-6) scale [20], or the Headache-Attributed Lost Time (HALT) Indices [21]. We considered the fact that there is not one single Patient-Reported Outcome scale (PROs) including the magnitude of the impairment that a person with a migraine attack or frequent migraine suffers.…”
Section: Debilitating Headachementioning
confidence: 99%
“…Different instruments have been used to assess illness-related productivity losses. Papers addressing migraine from a relevant systematic review (25) (28) and different versions of the HALT questionnaire (29). In our study, we combine both the administrative sick-leave database and the self-reported survey combining the WPAI used in some of the more recent studies (28) and the widely used MIDAS, which is also included in Slovenian national guidelines for migraine treatment (21).…”
Section: Discussionmentioning
confidence: 99%